Meluruskan Sejarah Proklamasi Kemerdekaan Indonesia: Suatu Kajian Terhadap Buku Teks Pelajaran Sejarah - Toto Suharya (CHRONOLOGIA, 2020)
Historical material around the proclamation includes knowledge that must become the collective memory of the Indonesian people. The history of the proclamation became a milestone for the success of the Indonesian nation in breaking away from colonialism. However, according to Hatta, there were many stories and writings that were not true about the Indonesian proclamation. In fact, the importance of writing history cannot be separated from the historical facts that were found. Thus, the objectives to be achieved in this study are to compile historical stories based on primary evidence and find the legitimacy of historical writing based on the theoretical point of view of historical writing for history textbooks. Meanwhile, the method used is literature study. The results show that the writing of the history of the proclamation of Indonesian independence in history textbooks does not reflect a narrative that has considered primary sources, both from the archives and the views of historical actors. The history of the proclamation that circulates in textbooks is dominated by historical stories based on the source of Adam Malik's book. Hatta's book of direct testimony which is more authentic, because as a direct actor in the incident, it is worth considering. Abstrak Materi sejarah sekitar proklamasi termasuk pengetahuan yang harus menjadi memori kolektif bangsa Indonesia. Sejarah proklamasi menjadi tonggak keberhasilan bangsa Indonesia dalam melepaskan diri dari penjajahan. Namun, menurut Hatta banyak tersiar cerita dan karangan yang tidak benar tentang proklamasi Indonesia. Padahal, kepentingan penulisan sejarah tidak lepas dari fakta sejarah yang ditemukan. Sehingga, tujuan yang ingin dicapai dalam penelitian ini adalah menyusun cerita sejarah berdasarkan bukti primer dan menemukan legitimasi penulisan sejarah berdasarkan sudut pandang teori penulisan sejarah bagi buku teks pelajaran sejarah. Sedangkan, metode yang digunakan adalah studi pustaka. Hasil penelitian menunjukkan bahwa penulisan sejarah proklamasi kemerdekaan Indonesia dalam buku teks pelajaran sejarah, belum mencerminkan narasi yang sudah mempertimbangkan sumber-sumber primer, baik dari arsip maupun pandangan pelaku sejarah. Sejarah peristiwa proklamasi yang beredar dalam buku teks, didominasi oleh cerita sejarah berdasarkan pada sumber buku Adam Malik. Buku kesaksian langsung dari Hatta yang lebih otentik, karena sebagai pelaku langsung dalam perisitwa tersebut layak untuk dipertimbangkan.